Gene-Based Therapeutics for Inherited Retinal Diseases - Fenner, Beau J.; Tan, Tien-En; Barathi, Amutha Veluchamy; Tun, Sai Bo Bo; Yeo, Sia Wey; Tsai, Andrew S. H.; Lee, Shu Yen; Cheung, Chui Ming Gemmy; Chan, Choi Mun; Mehta, Jodhbir S.; Teo, Kelvin Y. C. (Frontiers in Genetics, 2022)
Inherited retinal diseases (IRDs) are a heterogenous group of orphan eye diseases that typically result from monogenic mutations and are considered attractive targets for gene-based therapeutics. Following the approval of an IRD gene replacement therapy in 2017 for Leber’s congenital amaurosis due to RPE65 mutations, there has been an intensive international research effort to identify the optimal gene therapy approaches for a range of IRDs and many are now undergoing clinical trials. In this review we explore therapeutic challenges posed by IRDs and review current and future approaches that may be applicable to different subsets of IRD mutations. Emphasis is placed on five distinct approaches to gene-based therapy that have potential to treat the full spectrum of IRDs: (1) gene replacement using adenovirus associated virus (AAV) and nonviral delivery vectors, (2) genome editing via the CRISPR/Cas9 system, (3) RNA editing by endogenous and exogenous ADAR, (4) mRNA targeting with antisense oligonucleotides for gene knockdown and splicing modification, and (5) optogenetic approaches that aim to replace the function of native retinal photoreceptors by engineering other retinal cell types to become capable of phototransduction.